Student Transition During the Covid-19 Pandemic: A Case of Ho Chi Minh City (Proceedings of the World Conference on Children and Youth, 2022)
The purpose of this study is to examine further the reason students made a smooth transition from face-to-face to online learning during the COVID-19 pandemic in Ho Chi Minh City, Vietnam. To do this, the researcher compares the data collected for the previous study (Kang & Duong, 2021) with the data collected in 2022 still amid the pandemic. The previous study by Kang & Duong (2021) was on student perceptions of first-time online learning during the COVID-19 pandemic in Vietnam. According to the results of the data analysis by Kang & Duong (2021), flexibility (time, learning), live platform(s), such as Zoom and Google Classroom, comfort with online technologies, and lesson delivery were ranked in the top four helpful components of first-time online learning; internet access, technical problems, harder to pay attention, and lack of community were ranked in the top four challenging components. Based on the survey conducted in 2022, the researcher could find out further why the participants in the previous study (Kang & Duong, 2021) could make a smooth transition to their first-time online learning.
Keywords: COVID-19 pandemic; online learning; transition; social networks